Nagisavelia hikarui, a new genus and species of Mesoveliinae (Hemiptera: Heteroptera: Mesoveliidae) inhabiting shingle beaches in Japan - Watanabe, Kohei; Nakajima, Jun; Hayashi, Masakazu (Zootaxa, 2023)
A new genus and species of Mesoveliinae, Nagisavelia hikarui n.gen. and n.sp., is described from rocky intertidal beaches in Japan. The new taxon is compared to the other 10 genera of Mesoveliinae, and a character matrix for the identification of eight genera is provided. A key to facilitate the identification of the seven species of Mesoveliidae now reported from Japan is also provided.